Incorporación de yogurt de yuca en la alimentación de codornices macho en la etapa de crecimiento - LLuguay Bajaña, Martin José (2023)
Quail farming is a branch of poultry farming that aims to raise and improve quail production to use their products such as: eggs, meat, quail, among others. Quails, because they are very precocial animals and have high performance, need a food that is rich in protein (more than 22%), the average consumption is 25 g per day, it is necessary to remember the difference that exists between a food simple and a concentrate. The use of food alternatives for food animals leads us to complete research and experimentation, aiming for favorable results in an animal farm. A diet supplemented with by-products obtained from cassava has been determined as possible viable forms of production and fattening of quail. The incorporation of cassava yogurt in different quantities (15 ml, 20 ml and 25 ml) was evaluated, in which favorable results were presented both in weight gains and carcass performance, in addition, the use of probiotics and dewormers was replaced. commercials which improved the benefit – cost, fulfilling the objective of the research, reducing expenses and generating greater income for each dollar invested. Based on the results obtained, it was demonstrated that treatment 3 generated greater weight gains, weighing an average of 180.1 g of live weight in relation to treatment 0. It was observed that the quails showed a good state of health and body condition. based on the aforementioned treatment.